Cardiac arrest during laparoscopic cholecystectomy under general anaesthesia: A study into four cases - Gautam, B; Shrestha, BR (Kathmandu University Medical Journal, 2010)
Laparoscopic cholecystectomy (LapChole) has virtually superseded the more conventional open abdomen approach for the surgical treatment of symptomatic cholelithiasis. LapChole is however not a risk free procedure and serious, potentially fatal intra-operative complications can occur. Here we present case reports of four patients who suffered from intra-operative cardiac arrest during LapChole. All four recovered without residual morbidity and three of them underwent successful surgery in the same setting. No definite cause could be identified in any of the patients. We outline several possible mechanisms that could have been involved and discuss these events in face of published reports describing similar incidences. We infer that the creation of carbon-dioxide (CO2) pneumoperitoneum was involved in the causation of the cardiac arrest because all four incidences occurred within minutes thereafter. Although rare, such complications can be fatal and are thus demanding to the anaesthesiologist. Key words: Anaesthetic complications; carbon-dioxide pneumoperitoneum (CP); cardiac arrest; general anaesthesia; laparoscopic cholecystectomy DOI: 10.3126/kumj.v7i3.2738 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 280-288